Rabbit meat quality with an approach to its processing using spices or specific ingredients as antioxidants - Simone Mancini; Simona Mattioli; Alessandro Dal Bosco (World Rabbit Science, 2025)
Due to its low lipid content and high amounts of essential amino acids, rabbit meat is known for its excellent nutritional qualities, being very digestible and ideal for use in healthy diets. Unfortunately, rabbit meat has one of the highest lipid peroxidation susceptibilities, which restricts its use in processed food. Additionally, rabbit meat has some technological peculiarities that make it more challenging to incorporate into processed meat products, such as fragile bones, poor juiciness and a marginal anise-like flavour. But there may still be a demand for rabbit meat today. It might also be suggested as a substitute for traditional meat-based products, which are typically made with beef and pork, particularly for young children and the elderly. Moreover, ready-to-cook products, such as meatballs and burgers, may be well received by customers and new market trends could also emerge. The addition of spices can help improve the flavour and appeal of processed products made from rabbit meat while also increasing the antioxidant content and boosting nutritious value and shelf life. Furthermore, the use of natural antioxidants (spices) responds to the growing attention shown by consumers and food industries to avoid the use of synthetic molecules that diminish the products’ appeal.